2019
DOI: 10.1111/raq.12393
|View full text |Cite
|
Sign up to set email alerts
|

Status and recommendations for sustainable freshwater aquaculture in Brazil

Abstract: Brazil is a megadiverse country and is participant of fundamental environmental agreements for biodiversity conservation. However, the internal politics and the cultures that affect negatively the ecological integrity in Brazilian freshwater need to be improved on the condition of sustainable management. Scientific community, the government and stakeholders are in constant conflicts of goals. Meanwhile, the current model for Brazilian aquaculture shows problems of ecological impact due to the lack of appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 146 publications
0
32
0
5
Order By: Relevance
“…Considering that the cultivation of nonnative fish species in Brazil occurs mainly in cage nets (Lima et al 2018), it is possible to infer that escapes are inevitable; therefore, each cage net is a continuous source of nonnative propagules for the environment (Azevedo-Santos et al 2011). Damage such as alteration the diets of native fauna, alteration of the quality of the habitat due to eutrophication (Lima et al 2018), invasion of genotypes, increased production of interspecific hybrids and the introduction and transmission of nonnative parasites (Nobile et al 2020) are also reported to be due to the inopportune invasions associated with aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the cultivation of nonnative fish species in Brazil occurs mainly in cage nets (Lima et al 2018), it is possible to infer that escapes are inevitable; therefore, each cage net is a continuous source of nonnative propagules for the environment (Azevedo-Santos et al 2011). Damage such as alteration the diets of native fauna, alteration of the quality of the habitat due to eutrophication (Lima et al 2018), invasion of genotypes, increased production of interspecific hybrids and the introduction and transmission of nonnative parasites (Nobile et al 2020) are also reported to be due to the inopportune invasions associated with aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…According Nobile et al. (2019), one of the main challenges of Brazilian fish farming is to apply sustainable management alternatives in which sometimes the concept of sustainability adopted in public policies can conflict with that adopted by the scientific community, leading producers and stakeholders to make arbitrary decisions on this point. So, to ensure the application of the concept of development sustainable, the government of Brazil will need to ensure that aquaculture remains firmly linked to environmental legislation (Vieira, Oliveira, Crispim, & Cunha, 2016).…”
Section: Challenges In Aquaculture Productionmentioning
confidence: 99%
“…Increasing demand for farmed fish has enabled Brazil to reach a prominent position within the development of aquaculture. Hence, it is now one of the countries with the potential to meet the increasing worldwide demand for fish, and this has led to rapid expansion of aquaculture (Nobile et al., 2020).…”
Section: Introductionmentioning
confidence: 99%